Music as Thought : Listening to the Symphony in the Age of Beethoven - Bonds, Mark Evan (Book collections on Project MUSE., 2006)
Before the nineteenth century, instrumental music was considered inferior to vocal music. Kant described wordless music as "more pleasure than culture," and Rousseau dismissed it for its inability to convey concepts. But by the early 1800s, a dramatic shift was under way. Purely instrumental music was now being hailed as a means to knowledge and embraced precisely because of its independence from the limits of language. What had once been perceived as entertainment was heard increasingly as a vehicle of thought. Listening had become a way of knowing. Music as Thought traces the roots of this f.